Clinical assessment of growth performance, bone morphometry, bone quality, and serum indicators in broilers affected by valgus-varus deformity. (8th May 2019) - Guo, Yaping; Tang, Hehe; Wang, Xiangnan; Li, Wenting; Wang, Yanbin; Yan, Fengbin; Kang, Xiangtao; Li, Zhuanjian; Han, Ruili
ABSTRACT: The large economic losses caused by leg disorders have raised concerns in the broiler industry. Several types of leg disorders in broilers have been identified, such as tibial dyschondroplasia (TD), femoral head necrosis (FHN), and valgus-varus deformity (VVD). In this study, phenotypic changes associated with VVD were examined using clinical diagnosis, anatomical examination, measured growth performance, bone traits, and serum indicators. The incidence of VVD among the chicken population at a commercial facility in Tangshan China was 1.75% (n = 52, 000), distributed about 1:1 (n = 122), between females and males. A majority of chickens were characterized by a unilaterally abnormality, while appropriately 17.6% by bilateral abnormality. Approximately 97.9% of affected broilers were classified as the "valgus" type. Growth traits, including body weight, shank length, and shank girth, were significantly lower in chickens with VVD, while tibia and metatarsal bone indexes were about 1.3-fold higher in the affected birds than in the normal birds. Bone mineral density, bone breaking strength, and several serum indicators were significantly different between affected and normal broilers. Sparse and disarranged bony trabecular was observed in abnormal broilers by histological analysis. Generally, leg disorders are associated with compromised growth, bone quality, bone structure, and lipid metabolism. This study provides a reference for clinical diagnosis of VVD and lays a foundation for exploring its underlying mechanisms.